2018
DOI: 10.1016/j.healthplace.2018.07.002
|View full text |Cite
|
Sign up to set email alerts
|

School racial composition and lifetime non-medical use of prescription painkillers: Evidence from the national longitudinal study of adolescent to adult health

Abstract: We found evidence of an effect of school racial composition on the risk of misusing prescription painkillers over a decade later, over and above individual race, with higher risk of misuse reported among participants who had attended white schools. Black participants who had attended predominantly white schools were, on average, twice as likely to report lifetime misuse of prescription painkillers compared to blacks who had attended black schools.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 55 publications
0
1
0
Order By: Relevance
“…Not to be limited to rural and suburban areas, researchers note that the epidemic is urban as well [2]. White-majority spaces have even been tied to an increase among non-white populations in the risk of non-medical prescription painkiller misuse; longitudinal data revealed that black youth who attended majority-white schools were at higher risk a decade later of non-medical prescription painkiller misuse than black students who attended majority black schools [9]. Considering the substantial time and resources devoted to researching these issues, which afflict young and old, under-resourced and affluent, it is quite striking that only one primary commonality stands out in the current crisis: whiteness.…”
Section: Introductionmentioning
confidence: 99%
“…Not to be limited to rural and suburban areas, researchers note that the epidemic is urban as well [2]. White-majority spaces have even been tied to an increase among non-white populations in the risk of non-medical prescription painkiller misuse; longitudinal data revealed that black youth who attended majority-white schools were at higher risk a decade later of non-medical prescription painkiller misuse than black students who attended majority black schools [9]. Considering the substantial time and resources devoted to researching these issues, which afflict young and old, under-resourced and affluent, it is quite striking that only one primary commonality stands out in the current crisis: whiteness.…”
Section: Introductionmentioning
confidence: 99%